Association Between Erectile Dysfunction and Type 2 Diabetes Mellitus - Tamrakar, Dipesh; Bhatt, Dinesh Singh; Sharma, Vijay Kumar; Poudyal, Amod Kumar; Yadav, Binod Kumar (Journal of Nepal Health Research Council, 2021)
Background: Erectile dysfunction is a distressing complication of diabetes among male patients. Despite being a serious concern affecting sexual health, the issue regarding sexual dysfunction is seldom discussed by patients with physicians in developing countries. This study aimed to identify the prevalence of Erectile dysfunction and its association with other risk factors among type 2 Diabetic males attending the tertiary care hospital in Nepal.Methods: A cross-sectional hospital-based study was carried out in the Diabetes Out Patient Department of Tribhuvan University Teaching Hospital, Kathmandu, Nepal. 160 male patients with a history of Type 2 Diabetes Mellitus (T2DM) meeting the inclusion criteria were enrolled in the study with informed consent. A validated questionnaire; an abridge 5 item version of the International Index of Erectile Function (IIEF 5) was used to assess the erectile function where the score below 22 was considered as having erectile dysfunction. The severity of erectile dysfunction was categorized based on IIEF 5 score.Results: The prevalence of erectile dysfunction with varying degrees of severity was found to be 76.87% among T2DM male patients. There was a significant negative correlation of the IIEF5 Score with the duration of T2DM burden (r= -0.416, p<0.05) and the level of HbA1c (r= -0.391, p<0.05).Conclusions: There was a higher prevalence of erectile dysfunction among T2DM male patients that were also associated with poor glycemic control and the duration of T2DM burden.Keywords: Erectile dysfunction; international index of erectile function; type 2 diabetes mellitus